The Efficacy of Processing Strategies on the Gastroprotective Potentiality of Chenopodium quinoa Seeds - Abdalbasit Adam Mariod; Suzy Munir Salama (The Scientific World Journal)
The current study has been conducted to evaluate the effect of different processing techniques on the 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging capacity and the gastroprotective potential of Chenopodium quinoa red seeds in acute gastric injury induced by absolute ethanol in rats. Seven groups of female Sprague Dawley rats were assigned to normal and absolute ethanol (absolute EtOH) groups, given distilled water, reference control omeprazole (OMP, 20 mg/kg), pressure-cooked quinoa seeds (QP, 200 mg/kg), first stage-germinated quinoa seeds (QG, 200 mg/kg), Lactobacillus plantarum bacteria-fermented quinoa seeds (QB, 200 mg/kg), and Rhizopus oligosporus fungus-fermented quinoa seeds (QF, 200 mg/kg). One hour after treatment, all groups were given absolute ethanol, except for the normal control rats. All animals were sacrificed after an additional hour, and the stomach tissues were examined for histopathology of hematoxylin and eosin staining, immunohistochemistry of cyclooxygenase 2 (COX-2), and nitric oxide synthase (iNOS). Stomach homogenates were evaluated for oxidative stress parameters and prostaglandin E2 (PGE2). Gene expression was performed for gastric tumor necrosis factor alpha (TNF-α) and nuclear factor kappa of B cells (NF-kB). QB and QG recorded the highest DPPH scavengers compared to QF and QP. The gastroprotective potential of QB was comparable to that of OMP, followed by QF, then QG, and QP as confirmed by the histopathology, immunohistochemistry, and gene expression assessments. In conclusion, differently processed red quinoa seeds revealed variable antioxidant capacity and gastroprotective potential, while the bacterial fermented seeds (QB) showed the highest potential compared to the other processing techniques. These results might offer promising new therapy in the treatment of acute gastric injury.